Al-Qutb Atfiyyash and His Methodology in Authorship: The Manuscript “Al-Inshirah fi Bayan Shawahid al-Talkhis wa al-Miftah” as a Model - .chafai, kamel (El Omda in Linguistics and Discourse Analysis, 2026)
Many issues addressed by Al-Khatib in his book Summary, dealt with the most important axes on which rhetoric, with its different sections of the science, and not the only one who wrote in it, it was preceded by many Arabic scholars, as came after him many researchers in the field through many eras during which the science of rhetoric was included, so I wrote explanations, footnotes and summaries, and among the late ones who composed and explained those books, we find the pole Atfish from Ghardaia, Algeria, where he paid attention Great for this author, he explained all the poetic evidence contained in it, through his manuscript" Al-Inshirah in the statement of the evidence of the summary and the key. In this research, we will try to talk about the most important materials contained in it and the most important issues that he dealt with briefly by tracking his style in order to facilitate the recipient of that knowledge material, to conclude this work with the most important findings